2018
DOI: 10.1016/j.bbadis.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Metformin overcomes high glucose-induced insulin resistance of podocytes by pleiotropic effects on SIRT1 and AMPK

Abstract: Podocyte insulin sensitivity is critical for glomerular function, and the loss of appropriate insulin signaling leads to alterations and disorders featuring diabetic nephropathy. Energy-sensing pathways, such as AMP-dependent protein kinase (AMPK) and protein deacetylase SIRT1, have been shown to play an important role in insulin resistance. The absence of a stimulating effect of insulin on glucose uptake into podocytes after exposure to hyperglycemic conditions has been demonstrated to be related to a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 52 publications
0
46
0
1
Order By: Relevance
“…In rats with T2D, metformin increases the expression of nephrin and podocalyxin, both known to be downregulated or mislocalized in DKD . Treatment of primary rat podocytes with metformin activates protein deacetylase sirtuin 1 (SIRT1) and AMPK, and prevents high glucose‐induced downregulation of SIRT1 expression . Metformin also reduces high glucose‐induced apoptosis of podocytes in vitro .…”
Section: Does Ship2 Convey the Renoprotective Effects Of Metformin?mentioning
confidence: 99%
“…In rats with T2D, metformin increases the expression of nephrin and podocalyxin, both known to be downregulated or mislocalized in DKD . Treatment of primary rat podocytes with metformin activates protein deacetylase sirtuin 1 (SIRT1) and AMPK, and prevents high glucose‐induced downregulation of SIRT1 expression . Metformin also reduces high glucose‐induced apoptosis of podocytes in vitro .…”
Section: Does Ship2 Convey the Renoprotective Effects Of Metformin?mentioning
confidence: 99%
“…Our previous work indicated that metformin inhibits the in vitro expression of inflammatory cytokines and activation of nuclear factor‐κB induced by high glucose in rat glomerular mesangial cells. Emerging studies have shown that metformin can improve the blood glucose levels of DM patients through activating AMP‐activated protein kinase (AMPK), which also activates SIRT1 and regulates energy metabolism through FOXO1 . Wang et al revealed that although high glucose reduces the SIRT1 level and increases inflammatory factor expression in mesangial cells, SIRT1 activation downregulates the transcriptional activity of nuclear factor‐kappaB (NF‐κB) and inhibits inflammatory factor production and improves the inflammatory response in the kidney …”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have shown that metformin can improve the blood glucose levels of DM patients through activating AMP-activated protein kinase (AMPK), which also activates SIRT1 and regulates energy metabolism through FOXO1. 14 Wang et al 15 revealed that although high glucose reduces the SIRT1 level and increases inflammatory factor expression in mesangial cells, SIRT1 activation downregulates the transcriptional activity of nuclear factor-kappaB (NF-κB) and inhibits inflammatory factor production and improves the inflammatory response in the kidney. 15 The present work explores the role of metformin in mesangial cell proliferation, inflammation and ECM accumulation induced by high glucose and elucidates the underlying mechanism of metformin function on SIRT1/FOXO1-mediated autophagy to provide new insight into the development of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, AMPK and SIRT1 levels and activities were significantly declined in the kidneys T1DM, T2DM, and metabolic animal models and were correlated with the higher levels of ROS, apoptosis, and renal damage, whereas their activation afforded renoprotection (Declèves et al, ; Dugan et al, ; Eid et al, ; Lee et al, ; Piwkowska et al, ; Rogacka et al, , ; Xue et al, ; Yao et al, ; Zhang et al, ). These findings were also confirmed in the kidneys of our diabetic rats and in the HG‐treated mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AMPK levels and activities were significantly suppressed in the kidneys of diabetic patients and animals and were positively correlated with the severity of the degree of the DN, renal damage, and the clinical symptoms (Bandyopadhyay, Yu, Ofrecio, & Olefsky, 2006;Declèves, Mathew, Cunard, & Sharma, 2011;Eid et al, 2010;Lee et al, 2007;Rogacka, Piwkowska, Audzeyenka, Angielski, & Jankowski, 2014;Rogacka et al, 2018;Xu et al, 2012;Vitale, Mercuro, Silvestri, Fini, & Rosano, 2003). However, pharmacological activation of AMPK improved renal function, and attenuated the clinical-pathological features of DN in patients and experimental animals through reducing ROS levels, stimulating fatty acids oxidation, and inhibition of cellular inflammation, fibrosis, and apoptosis (Szrejder & Piwkowska, 2019).…”
mentioning
confidence: 99%